Progress and prospects of mechanotransducers in shear stress-sensitive signaling pathways in association with arteriovenous malformation. (August 2021) - Mahendra, Yoga; He, Mei; Rouf, Muhammad Abdul; Tjakra, Marco; Fan, Longling; Wang, Yeqi; Wang, Guixue
Abstract: Arteriovenous malformations are congenital vascular lesions characterized by a direct and tangled connection between arteries and veins, which disrupts oxygen circulation and normal blood flow. Arteriovenous malformations often occur in the patient with hereditary hemorrhagic telangiectasia. The attempts to elucidate the causative factors and pathogenic mechanisms of arteriovenous malformations are now still in progress. Some studies reported that shear stress in blood flow is one of the factors involved in arteriovenous malformations manifestation. Through several mechanotransducers harboring the endothelial cells membrane, the signal from shear stress is transduced towards the responsible signaling pathways in endothelial cells to maintain cell homeostasis. Any disruption in this well-established communication will give rise to abnormal endothelial cells differentiation and specification, which will later promote arteriovenous malformations. In this review, we discuss the update of several mechanotransducers that have essential roles in shear stress-induced signaling pathways, such as activin receptor-like kinase 1, Endoglin, Notch, vascular endothelial growth factor receptor 2, Caveolin-1, Connexin37, and Connexin40. Any disruption of these signaling potentially causes arteriovenous malformations. We also present some recent insights into the fundamental analysis, which attempts to determine potential and alternative solutions to battle arteriovenous malformations, especially in a less invasive and risky way, such as gene treatments. Highlights: Arteriovenous malformation occurs due to abnormalities in some mechanotransducers. Mutation in activin receptor-like kinase 1 could induce the malformation. Mutation in Endoglin is responsible in promoting the malformation. Flow-mediated signaling is less invasive target to treat the malformation.